Teaching Deficiencies of Teacher-Education Graduates of JRMSU-TC Based on the DepEd Criteria for Hiring Teachers - Liboon Jr., Alfredo; Rodriguez, Elmira (JPAIR Institutional Research, 2017)
The success of any educational system greatly relies on the competence of its teachers. That is why the Department of Education (DepEd) had set criteria in hiring competent and skillful teachers. The study aimed to identify the deficiencies of the JRMSU-TC applicants based on the DepEd criteria for hiring teachers. This further determined the percentage of disparity which item in the DepEd criteria the applicants deficit most and described whether they are above or below the minimum passing rate set by the DepEd. The researchers retrieved the Registry of Qualified Applicants (RQA) from the DepEd Office- Zamboanga Del Norte as instruments of the study and utilized descriptive evaluative design to measure the inadequacies of the applicants based on the DepEd criteria. Results revealed that the JRMSU-TC applicants highly deficit in teaching experience and English proficiency. Furthermore, the applicants are slightly below the DepEd minimum passing points. The results suggest that graduates should venture for the improvement of teaching competence and professional preparations. Also, the school needs to improve its instruction and assessment on the fundamental and major English subjects.